Novel Design of the Compound Sleeve and Stem Prosthesis for Treatment of Proximal Femur Bone Defects Based on Topology Optimization - Xue, Haowen; Bai, Haotian; Zhou, Rongqi; Wang, Jincheng; Zhou, Bin; Wang, Xiaonan; Luo, Wenbin; Zhao, Xin (Frontiers in Bioengineering and Biotechnology, 2022)
The loosening of traditional prosthetics is among the leading causes of surgical failure of proximal femoral bone defects. A novel compound sleeve and stem prosthesis was designed using an optimization methodology that combined an octet-truss porous structure with density-based topology optimization to improve stability, promote bone ingrowth, and enhance biomechanical properties. Biomechanical changes were assessed using finite element analysis. The distribution of stress, the strain energy density, and the relative micromotion in the optimized group were considered. The optimized sleeve prosthesis achieved a 31.5% weight reduction. The maximum stresses in the optimized group were observed to decrease by 30.33% and 4.74% at the back sleeve and neck part of stem prosthesis, with a 29.52% increase in the femur, respectively. The average stress in most selected regions in the optimized group was significantly greater than that in the original group (p < 0.05). The maximum relative micromotion decreased by 15.18% (from 63.9 μm to 54.2 μm) in the optimized group. The novel designed compound sleeve and stem prosthesis could effectively improve the biomechanical performance of next-generation prosthetics and provide a microenvironment for bone ingrowth. The presented method could serve as a model for clinical practice and a platform for future orthopedic surgery applications.